2012
DOI: 10.1590/s0102-67202012000200005
|View full text |Cite
|
Sign up to set email alerts
|

Achados principais de exames laboratoriais no diagnóstico de apendicite aguda: uma avaliação prospectiva

Abstract: -Background -Acute appendicitis is the most common surgical abdominal disease in the emergency room. ABCDDV/848RESUMO -Racional -Apendicite aguda é a doença abdominal cirúrgica mais comum nas unidades de emergência. Embora o diagnóstico seja clínico, a realização de exames complementares pode ser útil na dúvida diagnóstica. Objetivo -Avaliar as principais alterações de exames laboratoriais em pacientes com apendicite aguda, assim como sua relação com a fase evolutiva da doença. Métodos -Avaliação prospectiva … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…We also are able to reveal the capability of NLR to differentiate between simple and complicated appendicitis in children with sensitivity and cutoff value of ~0.85 and 6.59, respectively. Increasing levels of NLR will happen at the early stage of appendix inflammation and continue to increase in 85–95% patients with severe infection process such as in complicated appendicitis [7,13]. These findings were similar to other previous studies, with varying cutoff values between 5 and 8 [6,7].…”
Section: Discussionsupporting
confidence: 89%
“…We also are able to reveal the capability of NLR to differentiate between simple and complicated appendicitis in children with sensitivity and cutoff value of ~0.85 and 6.59, respectively. Increasing levels of NLR will happen at the early stage of appendix inflammation and continue to increase in 85–95% patients with severe infection process such as in complicated appendicitis [7,13]. These findings were similar to other previous studies, with varying cutoff values between 5 and 8 [6,7].…”
Section: Discussionsupporting
confidence: 89%
“…Patients sample size obtained in the interval of time considered was similar to that calculated in national and international clinical trials studying the same clinical subject 2 , 9 , 11 , 17 . The fact that acute appendicitis occurs mainly in young males is well established in medical literature 8 , 10 , and the sample included in this study showed the same pattern, considering that the number of males was almost two times the number of females, and the majority of the patients were 30 years of age or less.…”
Section: Discussionmentioning
confidence: 55%
“…Acute appendicitis is a condition that can be diagnosed mainly by its clinical features 8 , 10 , 19 , 20 ; however, in this sample only 4% had a purely clinical diagnosis. In 19,1% of them only one complementary exam was necessary (white blood cells count or ultrasound).…”
Section: Discussionmentioning
confidence: 69%
“…When criteria were analyzed in a isolated manner, as previously described by other authors, was noticed that CRP and segmented neutrophils show direct relation with the acute appendicitis stage. CRP was below 50 in patients in stage 1 and segmented neutrophils below 85% in 95% of the cases, and in stage 4, CRP was above 50 and segmented neutrophils above 85% in 60% of patients 10 .…”
Section: Discussionmentioning
confidence: 86%